Destination Image, Location and Price on The Interest Of Visiting Tourists in The Warm Water Tourism Park Umbul Temple - Krisnawati Setyaningrum Nugraheni; Guritno, Bambang (Media Wisata, 2023)
The purpose of this study was to determine the effect of destination image, location and price on the interest of visiting tourists at the Umbul Temple Warm Water Tourism Park. Data were obtained through documentation and questionnaires. The sample used in the study of 78 respondents. The results of the study are expected to provide useful information for managers and tourists. Then the results of the study were processed using the SPSS 23.0 application so that the data obtained were analyzed using multiple linear regression analysis, validity test, reliability test, F test, coefficient of determination test and hypothesis testing. The analysis shows that there is positive and significant influence of the destination image, location and price on the interest of visiting tourists at the Umbul Temple Warm Water Tourism Park.